Modern love and Poems of the English roadside, with poems and ballads - Meredith, George, 1828-1909 (Yale University Press, in association with the Beinecke Rare Book and Manuscript Library, 2012)
This is a collection of poetry by George Meredith from 1862 just after his wife had left him for the artist Henry Wallis.